2016
DOI: 10.1103/physrevlett.116.035501
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Emission from Breaking a Bamboo Chopstick

Abstract: The acoustic emission from breaking a bamboo chopstick or a bundle of spaghetti is found to exhibit similar behavior as the famous seismic laws of Gutenberg-Richter, Omori, and Båth. By use of a force-sensing detector, we establish a positive correlation between the statistics of sound intensity and the magnitude of tremor. We also manage to derive these laws analytically without invoking the concept of phase transition, self-organized criticality, or fractal. Our model is deterministic and relies on the exist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…These scale-free behaviours are usually considered to be signatures of collective phenomena and of importance in predicting material failure. Recently, similar scaling laws have been found in the compression of small and brittle porous materials [11][12][13][14], which may provide a correlation between avalanches that extend from geophysical scales (of the order of hundreds of kilometres) to sample scales (of the order of a few millimetres). The mean-field theory [15][16][17][18], neglecting the relevance of detailed physics, has been successfully applied to the explanation of these phenomena, together with universal scaling laws and exponents corresponding to experimental observations in brittle fracture [11][12][13][14][15][16][17][18].…”
Section: Introductionsupporting
confidence: 59%
“…These scale-free behaviours are usually considered to be signatures of collective phenomena and of importance in predicting material failure. Recently, similar scaling laws have been found in the compression of small and brittle porous materials [11][12][13][14], which may provide a correlation between avalanches that extend from geophysical scales (of the order of hundreds of kilometres) to sample scales (of the order of a few millimetres). The mean-field theory [15][16][17][18], neglecting the relevance of detailed physics, has been successfully applied to the explanation of these phenomena, together with universal scaling laws and exponents corresponding to experimental observations in brittle fracture [11][12][13][14][15][16][17][18].…”
Section: Introductionsupporting
confidence: 59%
“…Coal shows an Omori behavior with p = 0.95, similar to charcoal (p = 0.87) (Ribeiro et al 2015). In contrast, recent reports (Tsai et al 2016) gave much higher values for broken bamboo chopstick and a bundle of spaghetti with p = 1.68 and p = 3.53, respectively. The same tendency is seen for the numerical values of DM.…”
Section: Discussionmentioning
confidence: 78%
“…DM of charcoal was reported to be 1.2, which is identical with our data. Breaking of bamboo chopsticks lead to DM = 1.7 and that of a bundle of spaghetti gave DM = 0.8 (Tsai et al 2016). For earthquakes, large fluctuations of DM usually exist for different aftershock sequences (Hainzl et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…From a fundamental point of view, statistical laws in seismology have attracted the attention not only of geoscientists but also of physicists and mathematicians due to their signs of scale-invariance. Recent works have found that some of these laws also manifest in materials which exhibit crackling noise: porous glasses [1,2], minerals [3] and wood under compression [4], breaking of bamboo-sticks [5], ethanol-dampened charcoal [6], confined-granular matter under continuous shear [7], etc. Due to the difference between time, space and energy scales, these analogies have originated an important interest in the condensed-matter-physics community.…”
Section: Introductionmentioning
confidence: 99%